Heat capacity and thermodynamic functions of hollandite-type K0.17TiO1.9·0.061H2O. (October 2019) - Feng, Tao; Li, Liping; Shi, Quan; Chen, Yan; Li, Huixia; Li, Guangshe
Highlights: Hollandite-type K0.17 TiO1.9 with traced water was synthesized. A Schottky anomaly associated with the water at surface was discovered and discussed in heat capacity below T = 3 K. Heat capacity data and thermodynamic properties for hollandite-type K0.17 TiO1.9 ·0.061H2 O were determined. Abstract: The heat capacity of K0.17 TiO1.9 ·0.061H2 O has been measured by the use of a Quantum Design Physical Property Measurement System (PPMS) in the temperature range from 1.9 K to 302 K. An upturn below 3 K and weak bump at 7 K are observed and ascribed to Schottky anomaly and boson peak, respectively. The experimental data for K0.17 TiO1.9 ·0.061H2 O are fitted to a joint contributions of lattice vacancy, lattice vibration, Schottky anomaly and boson peak in the low temperature range ( T < 9 K), orthogonal polynomials in the middle temperature range (9 < T < 63) K, and a combination of Debye and Einstein functions in the high temperature range ( T > 63 K). The standard molar heat capacity, molar entropy, and molar enthalpy for K0.17 TiO1.9 ·0.061H2 O at T = 298.15 K are determined to be (64.2 ± 0.7) J·K −1 ·mol −1, (65.7 ± 0.7) J·K −1 ·mol −1, and (10.5 ± 0.1) kJ·mol −1, respectively, leading to a Gibbs energy of −(9.05 ± 0.09) kJ·mol −1 .